Common Core State Standards and Students with Severe Disabilities: An Introduction to the Special Issue. (September 2017) - Dukes, Charles; Darling, Sharon M.
This paper introduces a special issue of Research and Practice for Persons with Severe Disabilities, entitled "Common Core State Standards and Students with Severe Disabilities." The Common Core State Standards (CCSS) is a far-reaching policy intended to help all students be college and career ready. Yet, there seems to be quite a gap between interpretation of the standards and development of academic and social supports based on these standards for students with severe disabilities. In this introduction, some background is presented on the CCSS and why it is critical to examine the impact of standards adaptation and implementation for all students, including students with severe disabilities. Additionally, a rationale for the special issue is presented, along with a description of the special issue contents.